Encyclopedia and handbook of materials, parts, and finishes - Schwartz, Mel M. (CRC Press, 2016)
This encyclopedia serves the rapidly expanding demand for information on technological developments. In addition to providing information for manufacturers and assemblers of materials, components, systems. and structures, it is for use by managers responsible for technology development, research projects, R&D programs.